Tracking Inhibitory Control in Youth With ADHD: A Multi-Modal Neuroimaging Approach - Tremblay, Lescia K.; Hammill, Christopher; Ameis, Stephanie H.; Bhaijiwala, Mehereen; Mabbott, Donald J.; Anagnostou, Evdokia; Lerch, Jason P.; Schachar, Russell J. (Frontiers in Psychiatry, 2020)
Objective: Poor inhibitory control is a well-studied cognitive deficit in Attention Deficit Hyperactivity Disorder (ADHD), and is emerging as an endophenotype. It is measured with the Stop Signal Task (SST) with f-MRI, and reveals that ADHD youth show distinct brain regional activation. Here, we examine structural connectivity between these identified regions with the goal of identifying a white matter network of interest underlying this deficit. Method: Controls (N=16) and youth diagnosed with ADHD (N=56) were recruited through the Hospital for Sick Children. An f-MRI activation difference map testing inhibition with the SST in a prior study was co-registered with each participant’s diffusion tensor imaging (DTI). Probabilistic tractography was applied from these nodes, and white matter integrity indices such as fractional anisotropy (FA) were contrasted. Results: Tracts that connected the network nodes belonged primarily to the inferior fronto-occipital fasciculus (IFOF) and cingulum. ADHD subjects showed trend FA alterations between right inferior frontal gyrus (IFG) and right superior temporal gyrus (P= 0.09), right IFG and right posterior cingulate (P= 0.01), right anterior cingulate to posterior cingulate (p= 0.08), and between left middle temporal gyrus (BA 39) and left posterior cingulate (P=0.02). Conclusion: We expand on a potential endophenotype by bridging brain function, structure and inhibitory control. White matter disruptions occurred between frontal-temporal and cingulate nodes, which are known to belong to very distinct functional networks important to ADHD pathophysiology, that is, ventral attentional and default mode networks respectively. Findings may potentially represent a structural substrate of disrupted connectivity between these networks.